Government regulation, enforcement, and economic consequences in a transition economy: Empirical evidence from Chinese listed companies implementing the split share structure reform - Dequan Jiang; Shangkun Liang; Donghua Chen (China Journal of Accounting Research, 2009)
In a changing transition economy, Chinese government regulations that adopt the relatively simple bright line rule formula are enforceable in practice. Taking the early reform-oriented policies of the China Securities Regulatory Commission (CSRC) as an example, we find that the CSRC did not consider local enthusiasm for reform when allocating IPO resources because of the high enforcement costs involved. We also find that CSRC listed company regulations were enforced due to the lower costs involved in verifying regulatory violations, and that listed companies that completed the reform process were given priority in public refinancing. We present empirical evidence supporting the theoretical basis for the hypotheses outlined above. We also conclude that companies that completed the reform process in 2005 were of significantly higher quality and that the SEO regulation did not affect stock market efficiency. These findings enhance our understanding of the efficiency of government regulation in a transition economy.
Keywords: G32; G38; G15; 650; Government regulation; Enforcement; Economic consequences; Split Share Structure Reform (SSSR)